2001
DOI: 10.1155/s0161171201006457
|View full text |Cite
|
Sign up to set email alerts
|

On a theorem of Schur

Abstract: We study the ramifications of Schur's theorem that, ifGis a group such thatG/ZGis finite, thenG′is finite, if we restrict attention to nilpotent group. HereZGis the center ofG, andG′is the commutator subgroup. We use localization methods and obtain relativized versions of the main theorems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Hilton in [1] proved the following theorem Theorem 1.1. If G is a finitely generated group such that G is finite, then G/Z(G) is finite.…”
Section: Introductionmentioning
confidence: 99%
“…Hilton in [1] proved the following theorem Theorem 1.1. If G is a finitely generated group such that G is finite, then G/Z(G) is finite.…”
Section: Introductionmentioning
confidence: 99%
“…In a paper [1] published in 2001, we modified a famous theorem of Issai Schur, which asserts that if G is a group with center Z, such that G/Z is finite, then the commutator subgroup G = [G,G] is also finite. Our modification was twofold; in the first place, we confined ourselves to nilpotent groups G, so that we could use effective localization methods at an arbitrary family P of primes, and, second, we relativized the situation by replacing G by a pair of groups (G,N), where N is a normal subgroup of G. Then Z was replaced by the centralizer C G (N) of N in G, and [G,G] was replaced by [G,N].…”
Section: Introductionmentioning
confidence: 99%
“…We also considered in [1] a partial converse of Schur's theorem and its modification. In this partial converse, we showed that G/Z is finite if G is finite, provided that G is finitely generated (fg).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations